Restoration of the anti-proliferative and anti-migratory effects of 1, 25-dihydroxyvitamin D by silibinin in vitamin D-resistant colon cancer cells. Issue 2 (1st July 2015) - Bhatia, Vandanajay; Falzon, Miriam
Highlights: HT-29 cells were used as a model system for the intestinal epithelial. TNF-α increased Snail1 and Slug levels, and decreased vitamin D receptor levels. The TNF-α effects were reversed by the flavonolignan silibinin. HT-29 cells are resistant to 1, 25D's anti-proliferative and anti-migratory effects. Co-treatment with silibinin rendered HT-29 cells responsive to 1, 25D. Abstract: Colorectal carcinoma (CRC) is the third most common cancer in developed countries. A large fraction of cases are linked to chronic intestinal inflammation, with concomitant increased TNF-α release and elevated Snail1/Snail2 levels. These transcription factors in turn suppress vitamin D receptor (VDR) expression, resulting in loss of responsiveness to the protective anti-proliferative and anti-migratory effects of 1, 25-dihydroxyvitamin D (1, 25D). Experimental and epidemiologic evidence support the use of natural products to target CRC. Here we show that the flavonolignan silibinin reverses the TNF-α-induced upregulation of Snail1 and Snail2 in the 1, 25D-resistant human colon carcinoma cells HT-29. These silibinin effects are accompanied by an increase in VDR levels; Snail1 overexpression reverses these silibinin effects. Silibinin also restores promoter activity from a vitamin D-response element (VDRE) reporter construct. While 1, 25D had no significant effect on HT-29 and SW480-R cell proliferation and migration, co-treatment with silibinin restored 1, 25D responsiveness. In addition, co-treatment with silibinin plus 1, 25D decreased proliferation and migration at doses where silibinin alone had no effect. These findings demonstrate that this combination may present a novel approach to target CRC in conditions of chronic colonic inflammation.